1983
DOI: 10.1139/p83-144
|View full text |Cite
|
Sign up to set email alerts
|

Self-pulsing and chaos in acoustooptic bistability

Abstract: The output of a hybrid acoustooptic bistable device with delayed feedback is investigated. Depending on the input intensity, such a system exhibits periodic and chaotic behaviour. Period doubling up to period-8 with the reverse Lorentz sequence is presented. The sequence of bifurcations is truncated by the additive electrical shot noise and the multiplicative noise due to the laser intensity fluctuations. Frequency locked oscillations are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…The two successive regimes period-4 chaos and period-2 chaos illustrate the inverse cascade in the bifurcation diagram. These nonperiodic but chaotic regimes with a growing complexity are also in very good agreement with the behaviors observed in previous experimental investigations [4]- [9]. Another example of periodic regime is illustrated in Fig.…”
Section: (D)] Exhibits Subharmonic Peaks At Frequenciessupporting
confidence: 91%
See 1 more Smart Citation
“…The two successive regimes period-4 chaos and period-2 chaos illustrate the inverse cascade in the bifurcation diagram. These nonperiodic but chaotic regimes with a growing complexity are also in very good agreement with the behaviors observed in previous experimental investigations [4]- [9]. Another example of periodic regime is illustrated in Fig.…”
Section: (D)] Exhibits Subharmonic Peaks At Frequenciessupporting
confidence: 91%
“…This should allow the study of experimentally unexplored dynamical regimes. Whereas most of the optical systems reported up to the present use optical power [4]- [9], [16] or polarization as the operating variable [17], the oscillator reported in the following works with a nonlinearity which deals with optical wavelength. The potential advantage of such a system is the experimental easiness to use the wavelength to induce a nonlinear behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 2 The same is true in the analysis of chaos in AO bistability [12), where a sin 2 map has been approximated by a quadratic map.…”
Section: Etalon (For An Excellent Analysis See Ref (3))mentioning
confidence: 78%
“…Furthermore, the feedback can be positive or negative. In some cases, it has been shown that the incorporation of a positive feedback can give rise to hysteresis or bi-stability in a hybrid AO system with feedback [10][11][12]. In this case, the a is changed from its value in the absence offeedback, viz., c to [13] a=a0+/31_1 where I_ is the intensity of the first order, and fi is a feedback factor, proportional to the gain of the feedback amplifier and the conversion efficiency of the photo-detector.…”
Section: Acoustooptics With External Feedbackmentioning
confidence: 99%
“…(8), we find that the angular plane wave spectra of the various diffracted orders evolve according to (k2kxkmx) =j (9) In Eq. (9), the angular spectra of the various scattered orders 'm are defined according to the Fourier transform relation given as m(kxz)x{Wm(x,z)}JWm(x,xp(jkxx) (11) Also, in Eq. (9), the first term in the brackets on the right hand side represents the propagational diffraction effect.…”
Section: Introductionmentioning
confidence: 99%